THE ABILITY OF THE 2021/2022 ACADEMIC YEARS STUDENTS OF ENGLISH EDUCATION DEPARTMENT, ISLAMIC UNIVERSITY OF INDRAGIRI IN USING ADJECTIVE AND ADVERB IN A SENTENCE - Agus Mustajib; Syafrizal (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research was intended to find out the student’s ability in using descriptive adjective and adverb of manner in a sentence. The method used in this research was the descriptive quantitative research. The population of this research was the students of Islamic University of Indragiri. The sample of this research were 41 students (A and B classes) at the first semester of English Education Department, Islamic University of Indragiri in the academic 2021/2022 years. In collecting the data, this research used written test (essay) as the research instrument to use to find out the students’ ability in using descriptive adjective and adverb of manner in a sentence. Based on the result of test, the mean score of students’ ability in using descriptive adjective and adverb of manner in a sentence was 65.43. It was categorized enough level. Then for both of indicators, their ability in using adjective was higher than adverb. It can be proved by the result of the mean score was 73.10, and 61.04 for using adverb in a sentence. In conclution, the students in using adjective and adverb in a sentence were still confused to differentiate between two types of the grammatical structure.